Does acting extraverted evoke positive social feedback?. (1st June 2020) - Davydenko, Mariya; Zelenski, John M.; Gonzalez, Ana; Whelan, Deanna
Highlights: Randomly assigned confederates or participants to act extraverted or introverted. Interaction partners showed more positive social behaviors with extraverted actors. Behaviors were rated by the participant, confederate, and an observer. Extraverted behavior has the potential to evoke positive social feedback in others. Abstract: Personality traits describe average tendencies, yet momentary behaviors in trait domains vary widely. Notably, both dispositional introverts and extraverts experience greater positive affect when behaving in extraverted ways. We test a potential explanation: extraverted behavior may evoke more positive social feedback from others. In Study 1, participants who were randomly assigned to interact with confederates who acted extraverted (vs. introverted) displayed more positive verbal and nonverbal social behaviors during interactions. Behaviors were rated by the participant, confederate, and an observer (via video). Study 2 reversed roles; neutral confederates who interacted with participants who were randomly assigned to act extraverted (vs. introverted) displayed more positive social behaviors. This research extends previous findings by examining how enacted extraversion influences interaction dynamics.